Single Feed Square Aperture Circular Polarized Antenna - Abu Salim, S. A.; Abd. Aziz, M. Z. A.; Ahmad, B. H. (International Journal of Integrated Engineering, 2019)
In recent years, circular polarized antennas become more important in wireless communication systems because of the ability of radiating circular polarized wave. In this paper, the design of single-feed square-aperture antenna with and without reflector towards the circular polarized antenna performance is presented. The antenna made of square ground plane, square-aperture and a probing strip feed by using microstrip transmission line. The design has achieved a target axial ratio, which is less than 3 dB at frequency range of 4 GHz to 6.5 GHz. When a square ground plane reflector is integrated on the CP antenna for the unidirectional pattern, the presented antenna enhanced gain about 8 dB.